1968
DOI: 10.1111/j.1399-3054.1968.tb07227.x
|View full text |Cite
|
Sign up to set email alerts
|

The Minimum Growth Temperature of Obligately Thermophilic Bacteria as Influenced by Inhibitors in Complex Growth Media

Abstract: The inability of several obligately thermophilic bacteria to grow at or below 37°C in common laboratory media was shown to be caused by inhibitors present in these media. The inhibitors could be removed by extraction with chloroform and by adsorption on ion exchange resins or starch. It was concluded that they were of organic nature, probably bile acids. Four laboratory strains of Bacillus stearothcrtno‐philus grew readily at 37°C in detoxified media. With one of them (NCA 1503) growth was obtained at 34–35°C.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…More recently (Ljunger, 1968) , obligate thermophilic bacteria have been reported that grow at mesophilic temperatures when inhibitory substances are removed from the growth medium. But to the knowledge of the author the work of Oates et (1961Oates et ( , 1963Oates et ( , 1964 was the first known report of a mesophile being able to grow at elevated temperatures; however, recent work by Dowden et al (1968) suggests that a mesophilic strain of Bacillus subtilis can be adapted to grow at elevated tempera tures .…”
Section: Microorganismsmentioning
confidence: 99%
“…More recently (Ljunger, 1968) , obligate thermophilic bacteria have been reported that grow at mesophilic temperatures when inhibitory substances are removed from the growth medium. But to the knowledge of the author the work of Oates et (1961Oates et ( , 1963Oates et ( , 1964 was the first known report of a mesophile being able to grow at elevated temperatures; however, recent work by Dowden et al (1968) suggests that a mesophilic strain of Bacillus subtilis can be adapted to grow at elevated tempera tures .…”
Section: Microorganismsmentioning
confidence: 99%
“…More recently (Ljunger, 1968) , obligate thermophilic bacteria have been reported that grow at mesophilic temperatures when inhibitory substances are removed from the growth medium. But to the knowledge of the author the work of Oates et (1961Oates et ( , 1963Oates et ( , 1964 was the first known report of a mesophile being able to grow at elevated temperatures; however, recent work by …”
Section: Introductionmentioning
confidence: 99%